2020
DOI: 10.1002/htj.21997
|View full text |Cite
|
Sign up to set email alerts
|

Comparitive investigation of performance and emission features of methanol, ethanol, DEE, and nanopartilces as fuel additives in diesel‐biodiesel blends

Abstract: The usage of biodiesel blends is restricted due to its low fuel consumption and high thermal NOx. The current study exhibits the usage of four different fuel additives methanol, ethanol, diethyl ether, and NiO nanoparticles in Neem biodiesel blend (NB25) to shore up the usage of neem oil methyl ester. Performance and emission experimentation of a compression‐ignition engine fueled with NB25 having fuel additives were conducted at varying injection opening pressures (180, 210, and 240 bar) and static injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…At full load D80B10RW10, D70B20RW10, and D60B30RW10 gives 1.46%, 2.86%, and 3.91% lower Bthe than diesel, this is due to low‐calorific value of biodiesel and rice wine alcohol 38 . In general, Bthe decreased as mass flow rate increased because Bthe is inversely proportional to mass flow rate and calorific value, correlating this factor, Bthe mainly depend on mass flow rate because calorific value is fixed for particular fuels, where diesel‐biodiesel‐alcohol blend mass flow rate is found high as compared to diesel 42 to produce certain brake power, as brake power is constant for all fuels at particular load 14,31 therefore, it is known that higher blends of biodiesel gives low Bthe 56,57,62 due to low‐calorific value, low volatility, and high‐latent heat compared to low blend of biodiesel and diesel. But still all blended fuels have a closer value of Bthe to diesel this might be due to 10% rice wine alcohol that helps oxidation process and faster flame propagation for better performance of an engine.…”
Section: Resultsmentioning
confidence: 94%
“…At full load D80B10RW10, D70B20RW10, and D60B30RW10 gives 1.46%, 2.86%, and 3.91% lower Bthe than diesel, this is due to low‐calorific value of biodiesel and rice wine alcohol 38 . In general, Bthe decreased as mass flow rate increased because Bthe is inversely proportional to mass flow rate and calorific value, correlating this factor, Bthe mainly depend on mass flow rate because calorific value is fixed for particular fuels, where diesel‐biodiesel‐alcohol blend mass flow rate is found high as compared to diesel 42 to produce certain brake power, as brake power is constant for all fuels at particular load 14,31 therefore, it is known that higher blends of biodiesel gives low Bthe 56,57,62 due to low‐calorific value, low volatility, and high‐latent heat compared to low blend of biodiesel and diesel. But still all blended fuels have a closer value of Bthe to diesel this might be due to 10% rice wine alcohol that helps oxidation process and faster flame propagation for better performance of an engine.…”
Section: Resultsmentioning
confidence: 94%
“…Every time BDD blends are combusted they discharge harmful emissions which are left in the atmosphere and raise the levels of pollution. 15,16 To this issue, many authors have proposed the use of virtual techniques or software such as Diesel RK and ANSYS FORTE which provide values equivalent to real-time experimentation. The softwares are user-friendly where different biofuels and their blends can be added and probable performance and emission results can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…These observations with varying parameters are usually performed experimentally as there is no equivalent way for real‐time data. Every time BDD blends are combusted they discharge harmful emissions which are left in the atmosphere and raise the levels of pollution 15,16 . To this issue, many authors have proposed the use of virtual techniques or software such as Diesel RK and ANSYS FORTE which provide values equivalent to real‐time experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Moreover, it is evident from literature and concluded from a detailed study that nano-catalysts provide better conversion and yield for biodiesel conversion than conventional heterogeneous catalysts with better optimum conditions. [12][13][14][15][16][17] The studies have also revealed that the additive with biodiesel fuel mixtures augments the engine combustion characteristics and reduces the emissions; moreover due to nano-catalytic effects, raised CO 2 emissions and minimal O 2 emissions are also pellucid from studies made on biodiesels obtained from high FFA oils using inorganic nano-catalysts. 1,18 A concise overview of several nano-catalysts used so far for production of biodiesel has been tabulated in Table 1.…”
Section: Introductionmentioning
confidence: 99%